Aplikasi Tiktok Sebagai Media Pembelajaran Jarak Jauh Pada Mahasiswa Universitas Indraprasta PGRI - Anggun Citra Dini Dwi Puspitasari (Jurnal Educatio FKIP UNMA, 2021)
The purpose of this study was to determine the effectiveness of the use of the Zoom application as a distance learning medium which was carried out in order to break the Covid-19 chain. The method used in this research is descriptive qualitative with survey technique. This research was conducted at Universitas Indraprasta PGRI. The sample in this study was 20 people, consisting of teachers and school principals who were determined by purposive sampling. The instrument used is in the form of a questionnaire distributed online using a google form. Data analysis was carried out by calculating the percentage value of the questionnaire results and descriptive analysis with a quantitative approach. The results showed that 85.24% of teachers felt the benefits of the Tiktok application, although on the other hand there were still obstacles in the distance learning process, such as unstable internet quality.